Piętnasta nowelizacja Ustawy Zasadniczej Węgier z 2025 r. - Stradomski, Wojciech (Współczesne zmiany konstytucji w wybranych państwach europejskich: Pomiędzy partykularyzmem prawnym a wspólnotą doświadczeń, 2025)
THE FIFTEENTH AMENDMENT TO THE FUNDAMENTAL LAW OF HUNGARY OF 2025The article discusses the fifteenth amendment to the Fundamental Law of Hungary of 2025, which covers a wide range of constitutional changes. The amendments introduce new mechanisms, including the possibility of suspending citizenship, a constitutional ban on recreational drugs, the right to cash payments, as well as ideological issues such as the definition of family and a specific understanding of child protection, which takes precedence over other fundamental rights in the hierarchy of law. The author presents the political context: the crisis of confidence in the government and the emergence of a new political force shortly before the parliamentary elections, as well as the international environment of change. The analysis leads to the conclusion that the amendment is largely specific in nature, strongly linked to internal political dynamics and Fidesz’s current strategy, rather than European constitutional trends. These changes were not preceded by public and political debate and may have a significant impact on shaping support ahead of the 2026 parliamentary elections.